The Influence of Compensation, Motivation and Workload on Employee Performance at the Research and Development Planning Agency of Berau Regency with Job Satisfaction as an Intervening Variable - Wibowo, Ecuk (Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of compensation, work motivation, and workload on employee performance at the Badan Perencanaan Penelitian dan Pengembangan (Bapelitbang) Berau Regency, with job satisfaction as an intervening variable. A quantitative approach with a causal design was employed, involving 56 employees selected through a census technique. Data were collected via questionnaires and analyzed using path analysis and single factor analysis with AMOS software. The results indicate that compensation (estimate 0.347, p<0.001) and work motivation (estimate 0.367, p<0.001) positively and significantly affect job satisfaction, while workload (estimate -0.318, p=0.003) has a negative and significant effect. Compensation (estimate 0.245, p=0.007) and job satisfaction (estimate 0.489, p=0.002) positively and significantly influence employee performance, but work motivation (p=0.122) and workload (p=0.341) do not have a direct significant effect. Job satisfaction mediates the relationship between compensation, work motivation, and workload on employee performance, with R² values of 0.795 for job satisfaction and 0.883 for performance. The uneven distribution of compensation and workload, as evidenced by a satisfaction survey (44.64% dissatisfied) and the 2024 job analysis, significantly impacts satisfaction and performance. The study recommends designing fairer compensation policies based on workload and optimizing workload management to enhance job satisfaction and employee performance at Bapelitbang Berau Regency.